High-energy flexible supercapacitor-synergistic effects of polyhydroquinone and RuO2 center dot xH(2)O with microsized, few-layered, self-supportive exfoliated-graphite sheets - Muniraj, Vedi Kuyil Azhagan; Dwivedi, Pravin Kumari; Tamhane, Parikshit Shivaji; Szunerits, Sabine; Boukherroub, Rabah; Shelke, Manjusha Vilas (ACS Applied Materials & Interfaces, 2019)
An effective and straightforward route for tailoring the self-supporting, exfoliated flexible graphite substrate (E-FGS) using electrochemical anodization is proposed. E-FGS has essential features of highly exfoliated, few-layered, two-dimensional graphite sheets with the size of several tens of micrometers, interconnected along the axis of the substrate surface. The novel hierarchical porous structural morphology of E-FGS enables large active sites for efficient electrolyte ion and charge transport when used as electrode material for a supercapacitor. In order to effectively utilize this promising E-FGS electrode for energy storage purpose, a ternary composite is further synthesized with pseudocapacitive polyhydroquinone (PHQ) and hydrous RuO2 (hRO). hRO is synthesized via a sol-gel route, while electropolymerization is utilized for the electrodeposition of PHQ over E-FGS. Ultimately, the fabricated self-supporting E-FGS-based flexible supercapacitor is capable of delivering areal specific capacitance values as high as 378 mF cm(-2) at a current density of 1 mA cm(-2). Addition of the pseudocapacitive component to the E-FGS texture leads to similar to 10 times increase of the electrochemical charge storage capability. The imposition of mechanical forces to this flexible supercapacitor device results in trivial changes in electrochemical properties and is still capable of retaining 91% of the initial specific capacitance after 10 000 cycles. Alongside, the fabricated symmetrical solid-state flexible device exhibited a high energy density of 8.4 mu Wh cm(-2). The excellent performance along with the ease of synthesis and fabrication process of the flexible solid-state supercapacitor device using PHQ/hRO/E-FGS holds promise for large-scale production.
Keywords: graphite exfoliation; polyhydroquinone; ruthenium oxide; solid-state flexible supercapacitor; Ternary Composite